CPIA Africa, November 2021 : Assessing Africa’s Policies and Institutions - World Bank (World Bank, Washington, DC, 2022)
The Country Policy and Institutional Assessment (CPIA) 2021 Africa report provides an assessment of the quality of policies and institutions of International Development Association (IDA); eligible countries in Sub-Saharan Africa in calendar year 2020, at the height of the COVID-19 pandemic. The report analyzes the CPIA scores for 2020 to assess the extent to which the policies and institutions of the region's IDA countries are fostering sustainable growth, poverty reduction, and the effective utilization of development resources. The CPIA scores quantify the level of performance of each country against 16 criteria that represent the policy and institutional arrangements of an effective poverty reduction and growth strategy. The criteria are grouped into four clusters: economic management, structural policies, policies for social inclusion and equity, and public sector management and institutions. Countries are rated on a scale between 1 and 6, with high and rising scores signifying stronger policy and institutional frameworks.